Sie sind auf Seite 1von 6

# Convolutions of Complex Exponential Functions

Frank Massey

## Notation. The variable t is assumed to be restricted to nonnegative real values.

Prime and * denote differentiation and convolution with respect to t, e.g. f (t) = f/ t and
f(t) * g(t) = . Let F1(t;) = e-t and Fn(t;1,...,n) = Fn-1(t;1,...,n-1) * F1(t;n) and

## En(t;1,...,n) = 1n Fn(t;1,...,n). Thus Fn(t;1,...,n) = e-1t * * e-nt is the

convolution of exponential functions e-jt. If we write Fn(t) or En(t) it is assumed that the
parameters are 1,...,n. En(t) and Fn(t) are symmetric functions of the j since

## cj = [(1-j)(j-1-j)(j+1-j)(n-j)]-1 for distinct j while Fn(t;,...,) = tn-1e-t/(n-1)! for

equal j; see Ross [2, p. 272, 284].

In [1] we gave approximations to Fn(t) in the case of real j. Here we extend one
of the small time approximations to the case where the j may be complex, but occur in
complex conjugate pairs; see Propositions 3 and 4 below. We begin with a formula for
the convolution of two exponential functions with a pair of complex conjugate
parameters.

Proposition 1.

(1) 1 * f(t) =

(2) 1 * e-t =

## (5) e(-+it * e(--it =

1
Proof. (1) follows immediately from the definition of convolution. (2) follows
from (1). To prove (3) we use the following convolution identity

eit * e-it = =

## Finally (5) follows from (6) and (4). //

The next proposition shows that one can bound the convolution of a pair of
exponential functions with complex conjugate parameters in terms of the convolution of a
pair of exponential functions whose parameter is the real part of the complex parameters.
Note that te-t = e-t * e-t.

## (11) > te-t [ 1 - ]

Proof. One has sin t = . Therefore | sin t | . Since | cos(s) | < 1 except for a
finite number of points on 0 s t, one obtains (7). Similarly cos t = 1 - . Using (7) to
estimate sin(s) one obtains (8). Combining (8) with sin t = gives (9). Finally (10) and
(11) follow from (7) and (9). //

2
The following Proposition shows that Fn(t;1,...,n) for the case where complex 's
occur in conjugate pairs can be bounded by Fn(t;1,...,n) where the j are the real parts
of the j.

## Proposition 3. Suppose j = j + j where the j and j are real. Suppose j is

the complex conjugate of j-1 for j = 1, 2, , m and j is real for j = 2m + 1, , n. Let

m = 1 + 3 + + . Then

## Proof. We prove this by induction on m and n. In the case m = 0 there is nothing

to prove since all the are real. Consider the case m = 1 and n = 2. By (5) one has

## F2(t;1,2) = e(-+it * e(-+it = e(-+it * e(--it =

Using (10) and (11) and the fact that F2(t;1,2) = F2(t;1,1) = te-t one has

## which proves (12) and (13) in the case m = 1 and n = 2.

Now suppose (12) and (13) are true for m = k and n = 2k, i.e.

## (17) F2k(t;1,...,2k) F2k(t;1,...,2k) [ 1 - ] for 0 t .

We shall show (12) and (13) are true for m = k+1 and n = 2k+2. We have

Therefore

## Using (14) and (16) gives

3
| F2k+2(t;1,...,2k+2) | F2k(t;1,...,2k) * F2(t;2k+1,2k+2) = F2k+2(t;1,...,2k+2)

## (19) F2(t;2k+1,2k+2) F2(t;2k+1,2k+2) [ 1 - ]

Note that the right sides of (17) and (19) are positive for t in the range being considered.
Using (17), (18) and (19) one obtains

F2k+2(t;1,...,2k+2)

[F2k(t;1,...,2k) ( 1 - )] * [F2(t;2k+1,2k+2) ( 1 - )]

## F2k(t;1,...,2k) * F2(t;2k+1,2k+2) - [ t2F2k(t;1,...,2k) ] * F2k(t;1,...,2k) -

F2k(t;1,...,2k) * [ t2F2(t;2k+1,2k+2) ]

Since t2 is an increasing function, one has [t2f(t)]*g(t) t2 [f(t)*g(t)] if f(t) and g(t) are
non-negative. Therefore

F2k+2(t;1,...,2k+2)

## F2k(t;1,...,2k) * F2(t;2k+1,2k+2) - [F2k(t;1,...,2k)*F2k(t;1,...,2k)] -

[F2k(t;1,...,2k)*F2(t;2k+1,2k+2)]

= F2k(t;1,...,2k) * F2(t;2k+1,2k+2)( 1 - )]

= F2k+2(t;1,...,2k+2) ( 1 - )]

which proves (13) for m = k+1 and n = 2k+2. Therefore (12) and (13) hold in the case
n = 2m.

Now we prove (12) and (13) hold for n > 2m. One has

## (20) Fn(t;1,...,n) = F2m(t;1,...,2m) * Fn-m(t;2m+1,...,n)

= F2m(t;1,...,2m) * Fn-m(t;2m+1,...,n)

Therefore

## | Fn(t;1,...,n) | | F2m(t;1,...,2m) | * Fn-m(t;2m+1,...,n)

F2m(t;1,...,2m) * Fn-m(t;2m+1,...,n)

4
= Fn(t;1,...,n)

where we have used the fact that (12) holds for n = 2m. So (12) holds for general n. In
order to prove (13) suppose 0 t . Since (13) holds when n = 2m one has

F2m(t;1,...,2m) F2m(t;1,...,2m) [ 1 - ]

and the right side is non-negative. Combining this with (20) gives

## Fn(t;1,...,n) F2m(t;1,...,2m) * Fn-m(t;2m+1,...,n)

- [ t2F2m(t;1,...,2m) ] * Fn-m(t;2m+1,...,n)

Again using [t2f(t)]*g(t) t2 [f(t)*g(t)] for non-negative f(t) and g(t) one obtains

## Fn(t;1,...,n) F2m(t;1,...,2m) * Fn-m(t;2m+1,...,n) [ 1 - ]

= Fn(t;1,...,n) [ 1 - ]

## If we combine Proposition 3 with Theorem 4a in Section 2 one obtains the

following proposition which implies Fn(t) can be approximated by with a relative error
that is bounded by a constant times t2 for small t.

## Proposition 4. Suppose j = j + j where the j and j are real. Suppose j is

the complex conjugate of j-1 for j = 1, 2, , m and j is real for j = 2m + 1, , n. Let
m be as in Proposition 3, * = min{1,...,n}, be the mean of 1,,n, be the variance
and . Then

## | Fn(t;1,...,n) | (1 + A(t)) for t 0

Fn(t;1,...,n) [ 1 - ] for 0 t .

References.

## [1] Massey, F. J. and J. Prentis. "Approximations for Radioactive Decay Series."

2007.

5
[2] Ross, Sheldon M. Introduction to Probability Models, eighth edition. Academic
Press, San Diego, 2003.